Efeito das cadeias parafínicas sobre a gelificação e estabilidade de emulsões água em óleo - Freitas, Gizele Batalha (2019)
In the reservoir conditions, the components in the oil are in equilibrium. However, during the production of oil, fluid behavior changes can be observed, so that the oil starts to present a non - Newtonian behavior. Still, in the oil production stage, there is also the possibility that stable emulsions are formed, with water - in - oil (W/O) emulsions being most commonly noted. Wax is one of the main components responsible for altering the behavior of these systems. For this reason, the present work studies the influence of the different waxes chains on the gelation process in the model oil and the properties model emulsion W/O. Macrocrystalline (MA) and microcrystalline (MI) waxes were selected and used for the formulation of the systems. Thermal and structural characterizations of waxes were performed. The formulation of the emulsions was elaborated by varying the fractions of water, wax type, and surfactant. The main techniques used for the characterization of oils and emulsions were rheology, optical microscopy, and X-ray scattering analyzes (SAXS/WAXS).